Changes in the daily rhythm of lipid metabolism in the diabetic retina. - Qi Wang; Maria Tikhonenko; Svetlana N Bozack; Todd A Lydic; Lily Yan; Nicholas L Panchy; Kelly M McSorley; Matthew S Faber; Yuanqing Yan; Michael E Boulton; Maria B Grant; Julia V Busik (PLoS ONE, 2014)
Disruption of circadian regulation was recently shown to cause diabetes and metabolic disease. We have previously demonstrated that retinal lipid metabolism contributed to the development of diabetic retinopathy. The goal of this study was to determine the effect of diabetes on circadian regulation of clock genes and lipid metabolism genes in the retina and retinal endothelial cells (REC). Diabetes had a pronounced inhibitory effect on the negative clock arm with lower amplitude of the period (per) 1 in the retina; lower amplitude and a phase shift of per2 in the liver; and a loss of cryptochrome (cry) 2 rhythmic pattern in suprachiasmatic nucleus (SCN). The positive clock arm was increased by diabetes with higher amplitude of circadian locomotor output cycles kaput (CLOCK) and brain and muscle aryl-hydrocarbon receptor nuclear translocator-like 1 (bmal1) and phase shift in bmal1 rhythmic oscillations in the retina; and higher bmal1 amplitude in the SCN. Peroxisome proliferator-activated receptor (PPAR) α exhibited rhythmic oscillation in retina and liver; PPARγ had lower amplitude in diabetic liver; sterol regulatory element-binding protein (srebp) 1c had higher amplitude in the retina but lower in the liver in STZ- induced diabetic animals. Both of Elongase (Elovl) 2 and Elovl4 had a rhythmic oscillation pattern in the control retina. Diabetic retinas lost Elovl4 rhythmic oscillation and had lower amplitude of Elovl2 oscillations. In line with the in vivo data, circadian expression levels of CLOCK, bmal1 and srebp1c had higher amplitude in rat REC (rREC) isolated from diabetic rats compared with control rats, while PPARγ and Elovl2 had lower amplitude in diabetic rREC. In conclusion, diabetes causes dysregulation of circadian expression of clock genes and the genes controlling lipid metabolism in the retina with potential implications for the development of diabetic retinopathy.